Efektivitas Pembelajaran Daring Menggunakan Media WhatsApp terhadap Pemahaman Konsep dan Pengembangan Karakter Siswa pada Pembelajaran IPS - Fadila, Fanny Siti; Hanifah, Nurdinah; Saputra, Yudha Munajat (Jurnal Pena Ilmiah, 2021)
The purpose of this study was to determine the effectiveness of online learning usingmedia WhatsApp on understanding concepts and developing students' character in social studies learning. This study uses a descriptive method of correlation study with a survey design. The instruments used in this research are tests and questionnaires. The findings of this study indicate that: 1) Students' understanding of the concept of material events in the early days of the national movement is in good criteria with an overall average test score of 61.86, 2) The average percentage of student character development questionnaires is 78 ,74% with the character values used are religious values, honesty, discipline, independence, and responsibility so that based on data obtained from students who have done online learning usingmedia WhatsApp shows that the results of the questionnaire are on the effective criteria, 3) There are various factors that affect online learning by usingmedia WhatsApp on students and teachers. The factors that influence it are derived from internal factors and external factors. These factors can be a supporter or an obstacle to the effectiveness of the process of implementing online learning.